Management of high anal Fistula by Kshar Sutra (Texas Journal of Medical Science, 2022)
Anal fistula has been viewed as a surgical issue for ages due to its complex pathophysiology.Perianal fistulas affect 0.01 to 0.05% of the population and are frequently accompanied by patient pain and morbidity. Fistulae may also result from HIV, lymphogranuloma venereum, sacrococcygeal teratoma,Crohn's disease, trauma, TB, hidradenitis suppurativa, immunosuppression, sacrococcygeal teratoma, rectal duplication, and perianal actinomycosis. Long-term management of an anal fistula involves a significant risk of repeated recurrence and incontinence. In this study, 3 cases that represent a type of anal fistula with their treatment options, objectively weighed the advantages and disadvantages of each advancement in light of clinical outcomes, and attempted to identify the most successful anal fistula treatment methods